Digital sport marketing : concepts, cases and conversations - Seymour, Alan, 1949-; Blakey, Paul, 1969- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Digital sports marketing is a new, dynamic and rapidly evolving area that is having a profound impact on contemporary sport business. This is the only textbook to introduce core principles and best practice in digital sports marketing, focusing on key issues, emerging topics and practical techniques. The book surveys the new international digital landscape in sport business and explains how to apply digital marketing across key areas from fan engagement and public relations to strategic communication and branding. Every chapter includes discussion of key concepts, an in-depth case study, and an in-depth conversation with a leading industry practitioner that demonstrates how digital marketing works in the real world. Full of useful features, this is an essential textbook for any sport marketing, sport management, sport business or sport development course.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Marketing -- Technological innovations; Sports administration -- Technological innovations